Keanekaragaman Gastropoda Pada Habitat Karang Mati di Perairan Pulau Lahe Kabupaten Pohuwato - Makmur, Khairinissa Septiany; Kadim, Miftahul Khair; Kasim, Faizal; Nasaru, Faradila Putri; Asama, Windi Deptianingsih; Hilalunga, Adelin (Fakultas Kelautan dan Teknologi Perikanan - Universitas Negeri Gorontalo, 2025)
This study aims to assess the diversity, evenness, and dominance of gastropods in dead coral habitats, as well as the current environmental condition of the waters around Lahe Island, Pohuwato Regency. The research was conducted in April 2025. Gastropod sampling was carried out using the hand-picking technique during low tide conditions, employing a belt transect method measuring 50 × 3 meters across three observation stations. Water quality parameters were measured during the early stages of tidal retreat. Based on the results, gastropod species composition consisted of 34 species, 185 individuals, and 12 families (Buccinidae, Columbellidae, Conidae, Cypraeidae, Mitridae, Muricidae, Nassariidae, Pisaniidae, Strombidae, Tegulidae, and Turbinidae). The Shannon diversity index (H’) at all observation stations was < 2, indicating low diversity. The Simpson dominance index (D) at all stations was < 1, suggesting a high level of dominance. The evenness index (Ep) showed values approaching 0, indicating low species evenness. The water conditions around Lahe Island, Pohuwato Regency, indicate a moderate level of pollution based on the Shannon diversity index (H’), yet still support the survival of marine biota.